VAMP8 mucin exocytosis attenuates intestinal pathogenesis by Entamoeba histolytica - Cornick, Steve (Microb Cell, 2017)
The intestinal mucosa encounters a barrage of ingested insults within the host yet under homeostasis elegantly facilitates nutrient absorption and sustenance of the commensal microbiota. An essential defence mechanism employed by the host is limiting the spatial niche various microbes may occupy as executed by the fluid mucus layer. Pathogens that violate their restricted niche within the intestinal mucosa are first expelled by robust mucus secretion from goblet cells thus by-passing the need for an immune response. Surprisingly, while many pathogens are known to exert hyper-secretion of mucus from goblet cells, the mechanisms governing this event remain elusive. In a recent report by Cornick et al (MBio 8: e01323-17), we nominate SNARE-mediated exocytosis as the putative mechanism responsible for pathogen-induced mucus secretion from goblet cells. The vesicle SNARE VAMP8 on mucin granules within goblet cells is specifically activated following infection with the protozoan parasite Entamoeba histolytica that is known to induce potent hyper-secretion and coordinates mucin exocytosis. This secretion event is critical in fending off a pathogen, as cells lacking VAMP8 are prone to increased E. histolytica colonization and cytolysis through apoptosis. Failing coordinated mucus exocytosis and subsequent epithelial barrier destruction, the host mounts an immune response as a last line of defence.